Semaphorin3A/PlexinA3 association with the Scribble scaffold for cGMP increase is required for apical dendrite development - Szczurkowska, Joanna; Guo, Alan; Martin, Jacqueline; Lee, Seong-Il; Martinez, Edward; Chien, Chia Te; Khan, Tamor A.; Singh, Ravnit; Dadson, Doreen; Tran, Tracy S.; Pautot, Sophie; Shelly, Maya (Cell reports (Cambridge), 2022)
The development of the apical dendrite from the leading process of the bipolar pyramidal neuron might be directed by spatially organized extrinsic cues acting on localized intrinsic determinants. The extracellular cues regulating apical dendrite polarization remain elusive. We show that leading process and apical dendrite development are directed by class III Semaphorins and mediated by a localized cGMP-synthesizing complex. The scaffolding protein Scribble that associates with the cGMP-synthesizing enzyme soluble guanylate cyclase (sGC) also associates with the Semaphorin3A (Sema3A) co-receptor PlexinA3. Deletion or knockdown of PlexinA3 and Sema3A or disruption of PlexinA3-Scribble association prevents Sema3A-mediated cGMP increase and causes defects in apical dendrite development. These manipulations also impair bipolar polarity and leading process establishment. Local cGMP elevation or sGC expression rescues the effects of PlexinA3 knockdown or PlexinA3-Scribble complex disruption. During neuronal polarization, leading process and apical dendrite development are directed by a scaffold that links Semaphorin cue to cGMP increase. [Display omitted] •Sema3A co-receptor PlexinA3 interacts with the Scribble scaffold for cGMP synthesis•Sema3A/PlexinA3 association with Scribble mediates cGMP increase in dendrites•Sema3A/PlexinA3 mediate bipolar polarity and apical dendrite development via cGMP•Sema3A/PlexinA3-mediated localized cGMP increase may direct leading-edge polarity Szczurkowska et al. show that spatially directed Sema3A may promote development of the leading process and the apical dendrite via the co-receptor PlexinA3 by orchestrating localized cGMP increase on the scaffold protein, Scribble, at the leading edge of developing pyramidal neurons.